A new approach to actinic folliculitis: prophylactic narrowband ultraviolet B phototherapy. (6th January 2021) - Butt, S.; Dawe, R.; Blair, R.; Ibbotson, S.
Summary: Background: We have observed an increasing number of patients referred to the Scottish Photobiology Service (SPS), who were later diagnosed with actinic folliculitis (AF) and had positive phototesting results. Treatment options for AF are limited, with only a few reports in the literature. The use of prophylactic narrowband ultraviolet B (NB‐UVB) phototherapy for AF has not previously been described, and we report on this for the first time. Aim: To analyse the clinical characteristics, phototesting results and responses to treatment for patients with AF diagnosed by the SPS. Methods: We undertook a retrospective review over 10 years of all case notes of patients who were assessed and diagnosed with AF through the SPS, based at the Photobiology Unit, Dundee, UK. Results: All 10 patients were women. Mean age of onset was 25 years and mean time to referral for investigation was 7 years. The commonest site involved was the face, with the main clinical feature being monomorphic pustules appearing after sunlight exposure. The eruption could be provoked with iterative doses of broadband UVA irradiation in five patients. All patients were offered photoprotective advice and prophylactic NB‐UVB phototherapy. Five patients proceeded with phototherapy; four of these completed the desensitization course and all four reported either a delay in symptom onset or total prevention of rash induction, with complete efficacy of desensitization maintained for 3 years in one patient. Conclusion: We demonstrate the successful use of UVA provocation testing as a diagnostic tool in AF. Additionally, we recommend the use of prophylactic NB‐UVB phototherapy in AF as an effective and well‐tolerated approach.